Development of a School Profile Information System Based on Digital Branding to Support Promotional Strategies and Institutional Image with ISO 9126 Evaluation - Galih Yudha Saputra; Fachrul Rozie; Widyatmike Gede Mulawarman; Nurlaili Nurlaili (Poltanesa, 2026)
This study aims to develop a School Profile Information System based on digital branding to support promotional strategies and strengthen the institutional image of SMP Negeri 5 Samarinda. The developed system is designed as a web-based information and promotion medium to facilitate users in accessing school-related information effectively and interactively. The research employed the Research and Development (R&D) method to produce and evaluate the quality of the developed system. Data collection techniques included observation and interviews to identify user needs and system requirements. System quality evaluation was conducted using the ISO 9126 standard, focusing on four aspects: functionality, usability, portability, and reliability. The functionality and portability tests were analyzed using the Guttman scale and obtained a score of 1, indicating that the system was categorized as “feasible.” The usability aspect was evaluated using a Likert scale and achieved a percentage score of 83%, categorized as “very good.” Meanwhile, the reliability test also obtained a score of 1, indicating that the system met the reliability criteria. The results of this study indicate that the developed School Profile Information System is feasible to be used as a digital branding medium to support school promotional activities and improve institutional image.